Case Report: Two Families With HPDL Related Neurodegeneration - Micule, Ieva; Lace, Baiba; Wright, Nathan T.; Chrestian, Nicolas; Strautmanis, Jurgis; Diriks, Mikus; Stavusis, Janis; Kidere, Dita; Kleina, Elfa; Zdanovica, Anna; Laflamme, Nataly; Rioux, Nadie; et al. (Frontiers in Genetics, 2022)
There are recent reports of associations of variants in the HPDL gene with a hereditary neurological disease that presents with a wide spectrum of clinical severity, ranging from severe neonatal encephalopathy with no psychomotor development to adolescent-onset uncomplicated spastic paraplegia. Here, we report two patients from unrelated families presenting with severe and intermediate variations of the clinical course. A homozygous variant in the HPDL gene was detected in each patient; however, there was no known parental consanguinity. We also highlight reductions in citrate synthase and mitochondrial complex I activity detected in both patients in different tissues, reflecting the previously proposed mitochondrial nature of disease pathogenesis associated with HPDL mutations. Further, we speculate on the functional consequences of the detected variants, although the function and substrate of the HPDL enzyme are currently unknown.